The First Amendment and the Politics of Reproductive Health Care - B. Jessie Hill (Washington University Journal of Law & Policy, 2016)
This article explores the detailed nuances of contraception and reproductive care as distinct and individual entities within the healthcare system as a whole. Hill discusses the relationship between the First Amendment and reproductive rights, highlighting the discrepancies in judicial opinions based on whether or not reproductive rights are considered essential or elective care. Hill closes with a defense of reproductive rights, advocating them as an essential component of care as opposed to an elective moral choice.
Keywords: First Amendment; Politics; Reproductive health care; Abortion; Contraception; Regulation